CONTENT OF WOMEN HISTORY IN THE CURRICULUMOF HISTORY FOR SENIOR HIGH SCHOOL COMPARISON STUDY OF 1994, 2004, AND 2006 - Budiarti, Budiarti; Fahmi, Giri Rachmawati (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2013)
This paper reviewed the content of women in history in the 1994, 2004 (KBK), and 2006 curriculums. It uses content analysis method. The result of this research shows that the content of women history was not increased and in different in from curriculum to the others. In 1994 Curriculum, women history only focused on the woman organizations in national movement period. In KBK and KTSP, there was women history in Hinduism-Buddhism era, and in the colonial era. In KBK and 2006 curriculums, students could learn more although the material was not as complete as in 1994, but they can learn it from the internet. From the analysis result of the women history narration in history textbook in 1994 Curriculum, KBK, and 2006 curriculums, because of the patriarchy culture and political factor, the writing of women history was androcentric.